Theoretische und praktische Entwicklung einer aufgeklebten CFK Stahlbetonverstärkung unter Berücksichtigung der vollständigen Kompatibilität zum Betonstahl - Sedlmair, Roman (Karlsruher Reihe Massivbau, Baustofftechnologie, Materialprüfung, 2021)
Components made of reinforced or pre-stressed concrete often show deficits or damage that lead to the necessity of a strengthening action. In this case, strengthening and repair with externally bonded (EB) CFRP strips is a frequently used method. In this work this strengthening method is fundamentally modified. It differs from the currently used systems by the used adhesive and is characterized by deformation and bond characteristics which match the behavior of the reinforced concrete.